Remoção seletiva de cálcio e magnésio de licor sulfúrico concentrado em níquel utilizando-se extração por solventes convencional e sinérgica - Alexandre Silva Guimaraes (2018)
The product of the mixed hydroxide precipitate (MHP) re-leaching is a concentrated Ni sulfuric liquor generally containing Ca, Co, Cu, Mg, Mn and Zn at lower concentration levels. After purification for the removal of Cu, Co, Mn and Zn, the liquor is sent to the Ni electrolysis step, but the presence of Ca and Mg may hinder the operation efficiency. The present work aims to develop a route for the selective removal of Ca and Mg from concentrated Ni sulfuric liquor using solvent extraction. After selection of extractants, two purification strategies were investigated: (i) Removal of Ca with D2EHPA followed by removal of Mg with Cyanex 272 in individual circuits (conventional extraction), and (ii) Simultaneous removal of Ca and Mg with D2EHPA + Cyanex 272 mixture in one single circuit (synergistic extraction). Ni co-extracted with Ca and Mg can be recovered in staged operations of selective stripping with H2SO4. The stripping of Ca and Mg can be performed with H2SO4 or HCl leaving only 0.010.03% Ca and/or Mg in the organic solution. The extraction efficiency of Mg, the selective recovery of Ni and the stripping of Ca and Mg by HCl are maximized by the increase in temperature using the D2EHPA + Cyanex 272 system. The selection of extraction pH of Ca and/or Mg from concentrated Ni liquor is decisive to avoid the crowding out effect and the undesirable crud formation. The kinetics of extraction and stripping of Ca and Mg is rapid and favors the application of the D2EHPA + Cyanex 272 system in continuous operation. The purity of the final raffinate obtained with both strategies was higher than 99.9%. Equilibrium models were fitted to propose the extraction reactions and the real number of moles of D2EHPA and/or Cyanex 272 required to simultaneously extract Ca, Mg and Ni present in the liquor in real concentration was determined. FT-IR analyzes suggest that D2EHPA and Cyanex 272 participate in the cation exchange bond between H+ and M2+ ions, wherein M = Ca, Mg or Ni, resulting in organometallic complexes of type D2EHPA-M-Cyanex 272